DEPRESCRIBING PADA LANSIA DENGAN POLIFARMASI: DAMPAK TERHADAP OUTCOME KLINIS, KUALITAS HIDUP, DAN KEAMANAN OBAT – SUATU TINJAUAN LITERATUR - Riki Nova (Yayasan Nuraini Ibrahim Mandiri, 2025)
Background: Polypharmacy in older adults is associated with higher risks of adverse drug events (ADE), potentially inappropriate medications (PIM), hospitalisation, and mortality. Deprescribing has emerged as a structured clinical approach to optimise medication use, although its clinical outcomes remain inconsistent. Objective: This review aimed to summarise the current evidence regarding the effectiveness and safety of deprescribing interventions in older adults with polypharmacy. Methods: A structured literature review was conducted using PubMed/MEDLINE, Scopus, Google Scholar, and grey literature sources published between 2010–2025. Search terms included “older adults”, “polypharmacy”, “deprescribing”, and “medication review”. Eligible studies included clinical trials, quasi-experimental studies, and systematic reviews reporting deprescribing outcomes in older adults. Data were analysed narratively due to heterogeneity of methods and outcomes. Results: Most deprescribing interventions were based on explicit criteria (Beers, STOPP/START) or pharmacist-led medication reviews. Strong evidence supports deprescribing to reduce the number of medications and PIM in various clinical settings. However, findings regarding ADE, hospitalisations, and mortality remain inconsistent. The variability is partly explained by short follow-up duration, clinical heterogeneity, and differences in deprescribing models. Despite this, deprescribing appears safe, clinically acceptable, and well received by older adults and healthcare providers. Conclusion: Deprescribing improves medication optimisation and safety in older adults, although conclusive evidence on major clinical outcomes is still limited. Structured and multidisciplinary deprescribing approaches should be encouraged, particularly in primary care. Local studies are needed to evaluate long-term clinical effects and implementation feasibility in Indonesia.